Epidemiology of Cancer Incidence Estimates and Statistics 2000–2025: Analysis from National Cancer Registry Programme in India - Vemula, Sadanandam; Dhakshanamoorthy, Kalpanapriya (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Several hospital-based and population-based cancer registries (PBCRs) have been collecting cancer data systematically since 1982, according to the National Cancer Registry Programme-National Centre for Disease Informatics and Research, an initiative of the Indian Council of Medical Research.Objective Planning, observing, and assessing cancer control efforts require knowledge of current cancer statistics. This article's goal is to provide an update on cancer incidence projections for India by age groups, sex, and anatomical sites for the period 2020 to 2025.Materials and Methods The cancer incidence, patterns, trends, projections, and mortality from 28 PBCRs were analyzed in this study, along with the kind of therapy and stage of presentation of cancer patients from 58 HBCRs (N = 667,666) from the pooled analysis for the composite period 2012 to 2016. Data regarding the population at risk were obtained from the Indian Census (2001 and 2011) to estimate the age- and sex-stratified population. To gain a better understanding of the epidemiology of cancer, the states and areas of the nation were divided into PBCR groups.Results For both males and females, the districts with the highest age-adjusted incidence rates were Aizawl (269.4) and Papum Pare (219.8). It is anticipated that there will be 1392,179 cancer patients in India by 2020 and 1569,793 by 2025. In Delhi, the northern region of India, the incidence rates of tobacco-related malignancies were high (62.1% for men and 18.5% for women). High incidence rates were seen in the southern districts of Kollam (males: 52.9) and Bangalore (20.1), respectively. Age-adjusted rates (AARs) for males and females in Kolkata, East, were 42.3 and 13.7, respectively. Western cities with high AARs were Mumbai (18.2) and Ahmedabad Urban (54.3) for men and women, respectively. For lung cancer, in terms of male and female incidence rates, Aizawl district ranked highest at 38.8 and 37.9 per 100,000, respectively.Conclusion This study offers a methodology for evaluating cancer trends and status in India. To meet the national targets for noncommunicable diseases and the sustainable development goals, it will direct adequate support for action to boost efforts to promote cancer prevention and control.
Keywords: cancer incidence; lung cancer; breast cancer; tobacco-related cancer; relative proportion